COLLECTIVE PROCEDURAL TRANSACTIONS - Sabrina Nasser de Carvalho (Revista Eletrônica de Direito Processual, 2021)
The purpose of this article is to analyze the institute of the collective procedural transactions, either in relation to the legal foundations that support them, or with regard to the limits that condition it, so that the public elements related to the unavailability of these rights are duly observed.